2015
DOI: 10.1039/c5ra15434k
|View full text |Cite
|
Sign up to set email alerts
|

Thermally stable imidazoline-based sulfonate copolymers for enhanced oil recovery

Abstract: Novel imidazoline-based sulfonate copolymers (noted PAMDSCM and PAMPSCM) were successfully prepared by copolymerization of acrylamide (AM), acrylic acid (AA), 1-acrylamido ethyl-2-oleic imidazoline (ACEIM) with the sodium salts of 3-(diallyl-amino)-2-hydroxypropyl (NDS) or 2-acrylamido-2-methylpropane sulfonic acid (AMPS), respectively. The copolymers were characterized by infrared (IR) spectroscopy, 1 H nuclear magnetic resonance ( 1 H NMR) spectroscopy, pyrene fluorescence probe spectroscopy, viscosimetry an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 45 publications
(49 reference statements)
0
8
0
Order By: Relevance
“…As the easy-to-develop type I reservoirs are depleted, type II and III reservoirs, which are characterized by high temperature and salinity, become the next target; therefore, developing a chemically robust polymer for EOR is needed. Acrylamide (AM) copolymerized with proper functional monomers can yield an acrylamide-based copolymer having better temperature resistance, salt tolerance, and antishearing performance. Hydrophobically associating polymers (HAP) is a kind of modified acrylamide copolymer that can be obtained by introducing a small amount of hydrophobic groups (generally less than 2 mol %) into acrylamide-based copolymer backbone. The reversible three-dimensional network structures can be formed by the intermolecular association of the hydrophobic groups, which thus results in a significant increase in polymer solution viscosity and an excellent antishearing property. , Meanwhile, the appropriate increasing of temperature and mineralization can somewhat enhance the hydrophobic association and further increase the viscosity of the polymer solution. Therefore, in terms of thickening ability, HAP significantly outperforms HPAM and PAM as a result of hydrophobic associations.…”
Section: Introductionmentioning
confidence: 99%
“…As the easy-to-develop type I reservoirs are depleted, type II and III reservoirs, which are characterized by high temperature and salinity, become the next target; therefore, developing a chemically robust polymer for EOR is needed. Acrylamide (AM) copolymerized with proper functional monomers can yield an acrylamide-based copolymer having better temperature resistance, salt tolerance, and antishearing performance. Hydrophobically associating polymers (HAP) is a kind of modified acrylamide copolymer that can be obtained by introducing a small amount of hydrophobic groups (generally less than 2 mol %) into acrylamide-based copolymer backbone. The reversible three-dimensional network structures can be formed by the intermolecular association of the hydrophobic groups, which thus results in a significant increase in polymer solution viscosity and an excellent antishearing property. , Meanwhile, the appropriate increasing of temperature and mineralization can somewhat enhance the hydrophobic association and further increase the viscosity of the polymer solution. Therefore, in terms of thickening ability, HAP significantly outperforms HPAM and PAM as a result of hydrophobic associations.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1,2 ] Thus, there has been a long‐standing interest to understand the structures and properties of ion pairs. [ 3–6 ] In that regard, we have examined, especially, the behavior of ion pairs with different cations and either carbamate or dithiocarbamate anions in a variety of condensed media. [ 7–11 ]…”
Section: Introductionmentioning
confidence: 99%
“…Core displacement experiments showed that the polymer can improve oil recovery by 10-15%. 30,31 Liu et al prepared an amphoteric internal salt polymer containing imidazoline, which has good thinning, stress resistance, shear recovery, viscoelasticity, and temperature resistance. 32 Chitosan (CS) is a polycationic polysaccharide with unique physical, chemical properties and biological functionality, and it is a very promising natural degradable polymer material.…”
Section: Introductionmentioning
confidence: 99%
“…When the imidazoline structure was introduced, the polymer had higher temperature and salt resistance and shear stability. Core displacement experiments showed that the polymer can improve oil recovery by 10–15% 30,31 . Liu et al prepared an amphoteric internal salt polymer containing imidazoline, which has good thinning, stress resistance, shear recovery, viscoelasticity, and temperature resistance 32…”
Section: Introductionmentioning
confidence: 99%